Case report of successful treatment of patient with ruptured celiac artery aneurysm - Semenenko, I. A.; Yumasheva, V. A.; Alieva, N.; Yasnopolskaya, N. V.; Sysoev, V. M. (Frontiers in Surgery, 2025)
Celiac artery aneurysms (САА) represent the fourth most common visceral artery aneurysm. Despite its rarity, CAA carries a definite risk of rupture and/or other serious complications, which can be fatal. The reported rupture risk varies in the scientific literature, but it appears to range from 10% to 20%. CAA is often diagnosed at a late stage, after it has ruptured. There is currently no consistent approach to managing patients with CAA or its rupture. The aim of this case report is to present a successful minimally invasive treatment of CAA rupture.